Improving University Students' Writing Skills in Pakistan - María Isabel Maldonado García (Foxton Books, 2018)
The education system of Pakistan is not unified. Students mainly attend three types of schools with different languages as medium of instruction; private schools, public schools and religious schools (called locally madrassas). Even though mother tongue education is emphasized in education and literacy circles, Pakistan has not been able to implement policies that would allow all students to be taught in their mother tongue. Since mother tongue education (MLE) is not a reality, students have been facing many issues, especially in those regions of the country where Urdu is not spoken at home, rather a different regional language, dialect or language variety. A conference was held in Karachi, where data about the language situation of the country was collected at level one of the data collection and at level two, eighteen experts were interviewed, who provided a list of recommendations to address the matters found at level one, for the improvement of the writing skills of the students all over the country. The most important of these recommendations were to ensure that the students engage on enough writing practice and proper programs of instruction are set into place with properly trained instructors.